Investigation of reactive power distribution between two coils of inductive power transfer system by Poynting vector analysis. (March 2022) - Liu, Yuan; Zhang, Kehan; Hu, Aiguo Patrick
Highlights: The power transfer mechanism of reactive power of an IPT system through an airgap is studied by Poynting vector analysis. Analytical analysis of the imaginary part of the Poynting vector are derived to represent the reactive power. CST field simulation is undertaken to visualize the B/E field, and Poynting vector distributions in the proposed IPT system. Active and reactive power is compared between the Poynting vector and circuit analysis under perfect align and misalign conditions. The analytical analysis also shows the two mutual components of the Poynting vector contribute to the reactive power circulation between the two coils, and the self-components relates to the reactive power around each individual coil. Abstract: It is well known that real power can be transferred through the air gap between two coupled coils in an Inductive Power Transfer (IPT) system, but little is known about how the reactive power spatially circulates in the airgap between the coils. This paper investigates the reactive power distribution in an IPT system from the field point of view. The Magnetic field, electric field and resultant Poynting vector at an arbitrary point between two coupled coils are analysed by fundamental electromagnetic equations. In particular, the reactive power distribution is investigated under both open-circuit and loaded conditions. The measured results at the input and output of the two coupled coils show a good agreement with the Poynting vector and lumped circuit analysis. Furthermore, the Poynting vector analysis shows that the two mutual components of the Poynting vector contribute to reactive power circulation between the two coupled coils, while the self-components only affect the generation of reactive power around the individual coil. These results cannot be obtained by numerical or traditional lumped circuit analysis, and they are very useful for understanding the deep-level physical power transfer mechanism of an IPT system.